Listeria spp. e L. monocytogenes em carne bovina refrigerada e embalada a vácuo, equipamentos e ambiente de matadouros frigoríficos - FRANÇA, Leonardo (2008)
Intending to stipulate the parcel of Listeria spp. and L. monocytogenes in several sources, using the PCR techicic, 360 samples were analyzed in the period between november 2006 and february 2008, proceeding from 25 commercial abattoirs of five companies all licensed to export from some Brazilian States. Primers U1/LI1 for Listeria spp. and LM1/LM2 and LL5/LL6 for L. monocytogenes. Listeria spp. was detected in 19,72% of the samples, with percentage of 23% in the bone rooms, cold chamber and half carcass, 15% in beef cuts and 10% in the slaughter rooms. In the slaughterhouses it was detected in 19,42% in the A, 17,72% in the B, 22,95% in the C and 20% in the D and E. Analyzing the states, 16,34% in São Paulo, 23,94% in Mato Grosso do Sul, 14,06% in Goiás, 32% in Mato Grosso, 27,27% in Bahia and 14,28% in Pará were positive for its genus. No matter the pair of ‟primers‟‟ used for amplication, L. monocytogenes were detected in 14,72% of the samples, 20% in cold chambers, 15,83% in bone rooms, 13.33% in halfcarcass and in beef cuts and 10% in slaughter rooms. In the slaughterhouse A, 12,57% of the samples were detected positive‟, 11,39% in B, 21,31% in C and 13,33% in D e E. The bacterium was detected in São Paulo in 12,42% of positive samples, 14,08% in Mato Grosso do Sul, 12,30% in Goiás, 24%, in Mato Grosso, 27,27% in Bahia and 14,28% in Pará. The pair of primer LM1/LM2 revealed better efficience than the LL5/LL6 and although this last one has presented low efficiency to detection, the total of positive samples of L. monocytogenes of this research only was possible by the association of both. Listeria spp. and L. monocytogenes are largely propagated in the sources and studied places, and, therefore, disseminated in all slaughterhouses and analyzed States, excepting Minas Gerais. The results of this research revealed the necessariness of adoption of urgent providences about the control of the pathogen in the bovine slaughterhouses in Brazil and must alert the possibility of occurrence of outbreak of listeriosis of nutritious transmission, considering the occurrence and the frequency repetition here verified in half-carcass and beef cuts